Empowering Local Brands Through Strategic Branding: Case of MFD Studio - Firza Khalisha Rinjany (UNIVED Press, 2025)
The rapid growth of Indonesia’s fashion sector contributes significantly to the creative economy. This is influenced by the post-pandemic shift in consumer behavior, making the Indonesian fashion market more competitive. Indonesia’s local brands face challenges in competing in this Red Ocean market. One of the local brands facing this challenge is MFD Studio, a local fashion brand from Bandung. MFD Studio faces a challenge in building a strong brand identity and differentiating itself from competitors. This research was conducted using a qualitative approach with semi-structured interviews to explore internal and external perceptions of the brand. Moreover, secondary data analysis was conducted in journals, social media, and e-commerce. The data analysis was developed using brand audit analysis and value proposition canvas in terms of thematic analysis. The results identified that MFD Studio was experiencing challenges in terms of brand awareness and a mismatch between the visual elements and the values it wanted to deliver. According to the analysis results, a comprehensive improvement branding strategy is proposed, focusing on improving a more consistent brand visual identity, strengthening more precise values, and optimizing the use of digital channels to increase interaction with consumers. This strategy is expected to increase brand awareness, strengthen customer loyalty, and drived increased conversion, ultimately strengthening MFD Sttudio’s competitive position in the Indonesian fashion market.